Accumulation of cardiolipin and lysocardiolipin in fibroblasts from Tangier disease subjects - Fobker, Manfred; Voss, Reinhard; Reinecke, Holger; Crone, Christina; Assmann, Gerd; Walter, Michael (FEBS letters, 2001)
Tangier disease (TD) is an inherited disorder of lipid metabolism characterized by very low high density lipoprotein (HDL) plasma levels, cellular cholesteryl ester accumulation and reduced cholesterol excretion in response to HDL apolipoproteins. Molecular defects in the ATP binding cassette transporter 1 (ABCA1) have recently been identified as the cause of TD. ABCA1 plays a key role in the translocation of cholesterol across the plasma membrane, and defective ABCA1 causes cholesterol storage in TD cells. Not only cholesterol efflux, but also phospholipid efflux was shown to be impaired in TD cells. By use of thin layer chromatography, high performance liquid chromatography and time-of-flight secondary ion mass spectrometry, we characterized the cellular phospholipid content in fibroblasts from three homozygous TD patients. The cellular content of the major phospholipids was not found to be significantly altered in TD fibroblasts. However, the two phospholipids cardiolipin and lysocardiolipin, which make up minute amounts in normal cells, were at least 3–5-fold enriched in fibroblasts from TD subjects. A structurally closely related phospholipid (lysobisphosphatidic acid) has recently been shown to be enriched in Niemann–Pick type C, another lipid storage disorder. Altogether these data may indicate that the role of these phospholipids is a regulatory one rather than that of a bulk mediator of cholesterol solubilization in sterol trafficking and efflux.